The Influence of Leadership Style on Nurses' Work Motivation - M. Adila Rossa; Hardjito S. Darmojo; Partono Siswosuharjo (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
Nurses are healthcare workers who play a central role in the provision of healthcare services in hospitals. The level of nurse work motivation significantly determines the quality of nursing care, patient safety, and the successful achievement of organizational goals. One factor influencing nurse work motivation is the leadership style implemented by the ward head or nursing manager. Effective leadership is believed to create a supportive work environment, increase work morale, and encourage nurse involvement in the implementation of nursing care. Objective: This study aims to analyze the influence of leadership style on nurse work motivation in hospitals. Methods: This study used a quantitative design with a cross-sectional approach. The study sample consisted of 150 nurses working in inpatient units, selected using a total sampling technique. Data were collected using a structured questionnaire that measured nurses' perceptions of leadership style and work motivation levels. Data were analyzed univariately to describe respondent characteristics and variable distribution, and bivariately using the chi-square test to determine the relationship between leadership style and nurse work motivation. Results: The study showed that transformational leadership style was the most dominant style. Most nurses had high work motivation. There was a significant relationship between leadership style and nurse work motivation (p < 0.05), with transformational and participative leadership styles more associated with high work motivation than laissez-faire leadership styles. Conclusion: Leadership style significantly influences nurse work motivation. The implementation of an effective leadership style needs to be optimized to improve nurse work motivation and the quality of nursing services.